Development of motion tracking device to determine swing profile of a golf player - Atiqullah, Huzaifah; Mohd Nadzeri, Omar; Nasrul Hadi, Johari; Mohd Hasnun Ariff, Hassan; Mahadzir, Ishak@Muhammad; Zuazizi, Aziz (Springer, 2024)
Understanding the biomechanics during a golf swing is crucial. One way to understand it is by looking at the swing profile. Most of the time, the swing profile is assessed qualitatively by golfers. However, the qualitative evaluation is very subjective, and golfers have no quantitative data which they might refer to for optimization. The quantitative assessment, meanwhile, is expensive, has limited access, and focuses on a single-point measurement. This research aims to create a motion tracking device that captures a golfer’s swing profile. The device comprises an MPU6050, FireBeetle ESP32 microcontroller, and a 3.7v Li-Po battery. The commercial MMS sensor was the reference, and the MPU6050 was set to the nearest equivalent specifications. Based on the findings, the device matches the performance of the MMS, considering the bandwidth difference and the position of the MPU6050. Moreover, multiple devices can be used in which ESP-Now communication was embedded between the FireBeetle ESP32 boards to capture the swing profile of different body parts. The device offers golfers quantitative feedback on their golf swing, which can be analyzed for improvement.